The Influence of Financial Literacy on The Application of Fintech and Its Impact on The Sustainability of MSME Businesses - Amaliyah, Fitri; Hetika, Hetika (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The purpose of this study is to determine the level of literacy and application of fintech and its impact on the sustainability of MSME businesses in Tegal City. The method of data collection in this study was using questionnaires. Meanwhile, the sampling technique uses purposive sampling as many as 72 MSMEs. The hypothesis proposed, was statistically tested using WarpPLS version 7.0. The results of the study found that 1) financial literacy affects the use of fintech in MSMEs, 2) the use of fintech affects the business sustainability of MSMEs. 3) Financial literacy affects the sustainability of MSME business 4) The use of fintech is able to mediate the relationship between financial literacy and MSME business sustainability. Adequate financial literacy and the use of appropriate financial technology have a direct impact on the sustainability of MSME businesses so that they can compete in the market for a long time. MSMEs can carry out strategies to support business sustainability, namely through financial literacy and the use of fintech in their daily transactions. The implication for related parties is to be able to propose programs that can support the optimization of MSME business sustainability